2021
DOI: 10.2186/jpr.jpor_2019_629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on the prevention of bisphosphonate-related osteonecrosis of the jaw-like lesions in rats

Abstract: In this study, we aimed to investigate the effect of glucose metabolism on bone healing after tooth extraction in an osteoporosis rat model administered zoledronic acid (ZA) and dexamethasone (DX). Methods: In total, 24 male Wistar rats (4 weeks old) were randomly assigned to four groups: Control (subcutaneous physiological saline), ZD (subcutaneous ZA and DX twice a week), Ins+ZD (subcutaneous insulin followed by ZD treatment), and Met+ZD (oral metformin followed by ZD treatment). Blood was collected every tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In a glucocorticoid-induced osteoporosis model, oral metformin (200 mg/kg/day) had a dual protective effect, i.e., it both inhibited bone resorption and promoted bone formation in trabeculae (Zhao et al, 2019), Another study identified a similar osteoprotective effect of metformin in ketogenic diet-induced osteoporosis mice (Liu et al, 2019). In addition, metformin was able to prevent osteonecrosis, and the area of osteonecrosis in the jaws of rats given metformin was significantly reduced compared to the control group (Nakagawa et al, 2021). Besides preclinical studies, a study discovered that metformin use in patients with type 2 diabetes reduced the risk of osteoporosis/vertebral fracture by 30-40% (Tseng, 2021).…”
Section: Osteoporosismentioning
confidence: 99%
“…In a glucocorticoid-induced osteoporosis model, oral metformin (200 mg/kg/day) had a dual protective effect, i.e., it both inhibited bone resorption and promoted bone formation in trabeculae (Zhao et al, 2019), Another study identified a similar osteoprotective effect of metformin in ketogenic diet-induced osteoporosis mice (Liu et al, 2019). In addition, metformin was able to prevent osteonecrosis, and the area of osteonecrosis in the jaws of rats given metformin was significantly reduced compared to the control group (Nakagawa et al, 2021). Besides preclinical studies, a study discovered that metformin use in patients with type 2 diabetes reduced the risk of osteoporosis/vertebral fracture by 30-40% (Tseng, 2021).…”
Section: Osteoporosismentioning
confidence: 99%
“… Histopathological assessments Healing conditions 59 , 60 , 63 , 98 Histological sections show the soft tissue healing with the distance between the edges of the epithelia, and bone defects with the length of the necrotic bone exposed towards the oral cavity. Necrotic bone 49 , 57 – 59 , 64 , 69 , 72 , 96 , 100 The presence of necrotic bone represents the occurrence of MRONJ. The definition of necrotic bone depends on the number of confluent empty or karyolytic osteocytic lacunae.…”
Section: Assessment Of Mronj-like Lesions In Rodent Modelsmentioning
confidence: 99%
“… Empty bone lacunae 30 , 45 , 95 , 96 , 98 The proportion or the number of empty bone lacunae in a certain area indicates the degree of osteocyte loss, which present the bone necrosis. TRAP + osteoclast 44 , 49 , 57 , 58 , 64 , 67 , 69 , 72 , 93 , 95 101 The TRAP + osteoclasts present the bone resorption, commonly used indicators including numbers of osteoclast per area or per bone line. Osteoblast 30 , 44 , 49 , 64 , 67 , 93 , 97 Generally identified by hematoxylin-eosin staining or marked by alkaline phosphatase (ALP), bone morphogenetic protein-2 (BMP-2), or receptor activators of NF-κB ligand (RANKL), commonly used indicators including numbers of osteoclast per area or per bone line.…”
Section: Assessment Of Mronj-like Lesions In Rodent Modelsmentioning
confidence: 99%
See 2 more Smart Citations